Molecular epidemiology of Plasmodium species prevalent in Yemen based on 18 s rRNA. - Al-Mekhlafi, A.M.; Mahdy, M.A.; Azazy, A.A.; Fong, M.Y. (BMC, 2010)
Although P. falciparum is predominant, P. vivax, P. malariae and mixed infections are more prevalent than has been revealed by microscopy. This overlooked distribution should be considered by malaria control strategy makers. The genetic polymorphisms warrant further investigation.